Tanda Linguistik Lanskap Pecinan: Studi Kasus pada Artefak Budaya Kota Semarang - Monika Herliana; Memet Sudaryanto Memet Sudaryanto (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2026)
This study aims to describe the forms and functions of the linguistic signs in the linguistic landscape of Semarang's Chinatown, an area that represents the linguistic and cultural diversity of the Chinese community in Indonesia. The research focuses on identifying the forms of linguistic signs found in public spaces as cultural artifacts and analyzing their functions within the local social, economic, and cultural context. The data consists of linguistic signs on shop signs, banners, religious plaques, and directional signs, collected through field observation and photo documentation from August to October 2025. The analysis was conducted using a descriptive qualitative approach through observation, visualization, and interviews with temple administrators and local residents. The results indicate that the variation in the forms of linguistic signs includes monolingual, bilingual, and multilingual signs combining Indonesian, Mandarin, Hokkien, and Javanese. The functions of the linguistic signs are not only informational and commercial but also reflect strong cultural identity, symbolic, and religious functions, especially around the temple. These findings confirm that the linguistic landscape serves as a medium for representing Chinese ethnic identity as well as a space for socio-economic interaction in this heritage area. Validation was carried out through technique triangulation with expert interviews to ensure the accuracy of the analyzed forms and functions of the linguistic signs in the Semarang Chinatown area.